Learning Environmental Education to Students in Reducing Plastic Use Towards Zero Waste Indonesia - Yasin, Asramid; Putri, Amelia Retno Eka; Agustina, Dinda Tri; Agusrinal, Agusrinal; Gandri, La (MSJ : Majority Science Journal, 2024)
All sectors have realized that waste, especially plastic waste, has become a complex and serious environmental problem, not only in Indonesia, but also around the world. Plastic waste has a major impact on public health and environmental sustainability. In Indonesia, this negative impact is increasingly felt, with an increase in the amount of plastic waste that is not properly managed, polluting nature and damaging ecosystems. For this reason, there needs to be strategic efforts to reduce the use of plastic, one of which is through environmental education. This research explores the role of environmental education as a strategy to instill environmental awareness in students, so that they are more concerned about the impact of plastic waste. The method used in this study is library research, by analyzing various literature and previous research. The results show that environmental education can increase students' awareness of the dangers of plastic waste and the importance of better waste management. In addition, environmental education can also motivate students to apply the 3R (Reduce, Reuse, Recycle) principles in their daily lives. Practice-based learning and real actions have proven to be effective in arousing students' enthusiasm to reduce plastic waste. By involving students in activities directly related to waste management, they can feel the benefits and be motivated to participate in preserving the environment. Sustainable environmental education has great potential in shaping student behavior as agents of change towards a waste-free Indonesia in the future.